2020
DOI: 10.1186/s13287-019-1544-y
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1 enhances BMSC viability, migration, and anti-apoptosis in myocardial infarction via secreted frizzled-related protein 2 pathway

Abstract: Background: Bone marrow mesenchymal stem cell (BMSC) transplantation represents a promising therapeutic strategy for ischemic heart disease. However, its effects are hampered by the poor viability of transplanted cells and the hostile microenvironment of the ischemic region. Insulin-like growth factor-1 (IGF-1) is an important paracrine growth factor of BMSC and plays an important role in the properties of BMSC. Here, we investigated whether overexpressing IGF-1 could enhance the BMSC viability, migration, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 32 publications
3
46
0
Order By: Relevance
“…To detect the chemotactic ability of SHED-derived EVs, the chemotactic factors were investigated in the EV groups. It is acknowledged that TGF-β1 is one of the most important factors to drive MSC migration as well as IGF-1 [4,33]. Both factors were found in all EV groups in our study.…”
Section: Stem Cells Internationalsupporting
confidence: 59%
See 1 more Smart Citation
“…To detect the chemotactic ability of SHED-derived EVs, the chemotactic factors were investigated in the EV groups. It is acknowledged that TGF-β1 is one of the most important factors to drive MSC migration as well as IGF-1 [4,33]. Both factors were found in all EV groups in our study.…”
Section: Stem Cells Internationalsupporting
confidence: 59%
“…The process of natural bone repair is well organized and precisely controlled by numerous molecular signals. When a bone fracture occurs, a series of functional factors including platelet-derived growth factor (PDGF), transforming growth factor-β1 (TGF-β1), insulin-like growth factors (IGFs), and fibroblast growth factor-2 (FGF-2) is released into the extracellular space at the fracture site [3][4][5]. These factors collectively mediate the mobilization of bone marrow stromal cells (BMSCs), which proliferate and subsequently differentiate into osteoblasts to contribute to new bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…In our recently published study, we reported that in rat with acute myocardial infarction, transplantation of bone marrow mesenchymal stem cell overexpression insulin-like growth factor-1 greatly reduced infarct volume and myocardial fibrosis. These effects were mediated by the expression of SFRP2 [30]. Therefore, we propose that the association of SFRP2 and increased ECV fraction could be reflective of SFRP2 acting as a compensatory factor (rather than a risk factor) to counteract myocardial fibrosis during the development of HF.…”
mentioning
confidence: 87%
“…IGF-1 is another GF that was used to enhance the efficiency of stem cell therapy of MI. Lin and colleagues transplanted BMSCs overexpressing IGF-1 to rats with acute MI [ 83 ]. IGF-1 overexpressing BMSCs had higher survival and proliferation, protected cardiomyocytes from apoptosis, and reduced the infarct size.…”
Section: Genetically Modified Stem Cell For MI Treatmentmentioning
confidence: 99%